2019
DOI: 10.3390/ma12050757
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characteristics of Ethylene Bis(Stearamide)-Based Graphene-Modified Asphalt

Abstract: In this study, graphene-modified asphalt (GMA) was prepared from SK-70# matrix asphalt and ethylene bis(stearamide) (EBS). Based on the uniform design method, a model was created using Data Processing System (DPS) software and First Optimization (1stOpt) software using the graphene mixing amount, EBS mixing amount, shear rate, shear time, and shear temperature as factors and using the asphalt penetration, softening point, force ductility, SHRP-PG test, and multistress creep recovery data as indices. Calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 47 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, asphalt type and chemical composition also affected the fatigue resistance of SBS-latex-modified asphalt dramatically [35,36]. It was found that, with the same SBS latex dosage, the fatigue temperature values of modified asphalts A were all higher than that of modified asphalts B, indicating that modified asphalts B had better fatigue resistance performance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, asphalt type and chemical composition also affected the fatigue resistance of SBS-latex-modified asphalt dramatically [35,36]. It was found that, with the same SBS latex dosage, the fatigue temperature values of modified asphalts A were all higher than that of modified asphalts B, indicating that modified asphalts B had better fatigue resistance performance.…”
Section: Resultsmentioning
confidence: 99%
“…Another promising category of modifying agents for bitumen is represented by graphene [13,14], able to improve the bitumen stiffness at high temperatures and the deformation recovery [15], as well as to reduce the cost of the entire pavement life cycle [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…According to the SHRP PG specification, the parameters of | G* |/sin δ and | G* |·sin δ are calculated from | G* | and δ , and utilized as the evaluation indexes of rutting potential and fatigue resistance of asphalt binder. The physical meaning of | G* |·sin δ is the viscous component in | G* | (i.e., the dynamic shear modulus) and it directly represents the dissipated strain energy during the dynamic loading cycles [ 7 , 8 ]. However, the subsequent verification works demonstrated that the performance of asphalt mixture and pavement in the field generally cannot be revealed very well from the binder parameters (| G* |/sin δ , | G* |·sin δ , etc.).…”
Section: Introductionmentioning
confidence: 99%